2021
DOI: 10.3390/su13041728
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Spatial Association and Influencing Factors of Carbon Emissions from the Chinese Construction Industry

Abstract: As the world’s largest carbon emitter, China is under enormous pressure to decrease carbon emissions. With the economic development in recent years, China has increased its investment in infrastructure, and the construction industry has become an essential source of carbon emissions. Using the social network analysis (SNA) methodology, this article analyzes the evolutionary characteristics of the spatial correlation network for carbon emissions in the construction industry from 2003–2017 and its affecting fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 42 publications
(58 reference statements)
1
5
0
1
Order By: Relevance
“…Centrality represents the position and function of each network node and its central location, including weighted degree centrality (C WD ), degree centrality (C D ), betweenness centrality (C B ), and closeness centrality (C C ). Based on previous studies, the centrality metrics of SNA can validly measure the position and function of nodes in a complex network, which can assist researchers in understanding the importance of the roles played by individual nodes in the associated network [24]. Thus, the current study adopted a mixedmethod approach that included bibliometric analysis and SNA to construct a keyword co-occurrence network (KCN) [25,26].…”
Section: Social Network Analysis and Centrality Metricsmentioning
confidence: 99%
“…Centrality represents the position and function of each network node and its central location, including weighted degree centrality (C WD ), degree centrality (C D ), betweenness centrality (C B ), and closeness centrality (C C ). Based on previous studies, the centrality metrics of SNA can validly measure the position and function of nodes in a complex network, which can assist researchers in understanding the importance of the roles played by individual nodes in the associated network [24]. Thus, the current study adopted a mixedmethod approach that included bibliometric analysis and SNA to construct a keyword co-occurrence network (KCN) [25,26].…”
Section: Social Network Analysis and Centrality Metricsmentioning
confidence: 99%
“…Global warming caused by greenhouse gases is a global environmental problem that has become a significant threat to the survival of humans and other species (Lu et al, 2020). Among the many greenhouse gases, CO 2 accounts for about 70% (Li and Chen, 2020)and is the most important anthropogenic greenhouse gas in the environment (Li et al, 2021). To fight global warming, it is necessary to ensure that countries worldwide effectively reduce CO 2 emissions (Lu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the construction industry accounts for more than 40% of the world's energy consumption and 36% of the world's CO 2 emissions (Li et al, 2021). It is an important pillar industry of China's national economy and a resource-intensive industry (Wang and Feng, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Countries and organizations all over the world are contributing to carbon emission reduction (Ma et al, 2020). As the world's largest carbon emitter, China is under enormous pressure to decrease CO 2 emissions (Li et al, 2021). China has committed to achieving carbon dioxide emissions peaking by 2030 and carbon neutralization by 2060 (Zheng et al, 2019).…”
Section: Introductionmentioning
confidence: 99%